THE INTERPRETATION OF AULIYĀ CONTEXTUAL MEANING IN THE QUR'AN (STUDY OF C.S PEIRCE SEMIOTICS THEORY) - Fatimah, Fatimah; Lutfiah, Winona (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
The term auliyā' is usually interpreted by the community as the leader, this is supported by interviews conducted by the researchers as well as the reports regarding the change in the meaning of auliyā in surah al-Maidah verse 51 by the Ministry of Religion from 'leader' to 'friend' which was again widely discussed at the beginning of June 2021. The narrow understanding of the auliyā term which is allowed to continue has implications for the reduction of the meaning of the Qur'an. Therefore, this study aims to discuss the interpretation of the differentiation of the auliyā' term meaning contextual in the Qur'an based on a semiotic study ; Charles Sanders Peirce. This study used qualitative text analysis methods, especially qualitative content analysis in analyzing the available data. By using the Semiotics approach, this study interpreted the term Auliyā' using the tracheotomy theory of C.S. Peirce. The results of this study indicated that the interpretation of the term auliyā' was not only limited to the leader but was also interpreted as a helper, protector, friend, lover, master, and guardian. This study recommends to academics to develop further the substance of research in addition, this research is also expected to be additional information for readers that the term auliyā' is not only limited to the meaning of leader so the judgmental attitudes that caused the reduction of the meaning of the Qur'an no longer occurred.الملخصعادة ما يفسر المجتمع مصطلح الأولياء على أنه زعيم فقط ، ويدعم ذلك المقابلات التي أجراها المؤلف وكذلك الأخبار المربكة فيما يتعلق بالتغيير في معنى الأولياء في سورة المائدة الآية 51 من قبل وزارة الدين من.